Metals Influence Structure and Solubility of Fucoidan and Strategy of Metal Removal in Fucoidan - Luo, Xuegeng (Auckland University of Technology, 2021)
Undaria pinnatifida is a widely distributed species of brown seaweed in New Zealand. Fucoidan is a sulfated polysaccharide which is extracted from U. pinnatifida. Its numerous bioactivities have been studied for several decades. Fucoidan is heterogenous polysaccharide and its structure is not constant. With degradation of the molecular weight of fucoidan across the same species, the structure and components are also not constant. However, in Undaria pinnatifida there are few reports that show a molecular weight of fucoidan below 10kDa. Fucoidan should be highly soluble, however, it was found that the fucoidan did not completely dissolve and unknown sediments were found. Therefore, this research is aimed to find out the sugar component of fucoidan fraction among 10kDa to 1kDa, and to find out a good agent to solubilize the solubility of fucoidan. Here the interaction of polysaccharide and metals might cause a metal-sugar complex gel to insolubilize fucoidan. EDTA-Na2 was chosen as metal removal agent which detected the amount of sediment present and was used to verify the efficacy of removing metals from fucoidan. The fraction of fucoidan among 10kDa to 1kDa was divided into >10kDa, >3kDa, <3kDa, >1kDa and <1kDa, all of which were separately treated with EDTA-Na2 and Milli-Q water. Microwave plasma – atomic emission spectroscopy (MP-AES) was used to determine the metal contents in fucoidan from U. pinnatifida, and LC/MS was used to detect the chemical composition of fucoidan. Infrared Spectroscopy was used to measure the total sugar content within the 10kDa and 3kDa fraction. To conclude, EDTA-Na2 showed good efficacy in the removal of divalent and transition metal ions. Fucoidan with different treatments had different sugar content, which would indicate that the structure correlated with metal content.
Keywords: Fucoidan; EDTA-Na2; Metal; Interaction